2020
DOI: 10.33073/pjm-2020-039
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Phosphate-Solubilizing Soil Bacteria Promotes In vitro Growth of Solanum tuberosum L.

Abstract: The capacity of four bacterial strains isolated from productive soil potato fields to solubilize tricalcium phosphate on Pikovskaya agar or in a liquid medium was evaluated. A bacterial strain was selected to evaluate in vitro capacity of plant-growth promotion on Solanum tuberosum L. culture. Bacterial strain A3 showed the highest value of phosphate solubilization, reaching a 20 mm-diameter halo and a concentration of 350 mg/l on agar and in a liquid medium, respectively. Bacterial strain A3 was identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…In this study, a highly effective P-solubilizing strain was screened and identified as Bacillus megaterium , with a P-solubilizing capacity of 461.86 mg·L −1 after 7 days of incubation in NBRIP medium, which was higher than the Bacillus strain P1 (392.56 mg·L −1 ), P2 (296.77 mg·L −1 ), P58 (371.16 mg·L −1 ), Bacillus subtilis KSP-11 (66.4 mg·L −1 ) ( Hanif et al, 2015 ), and Bacillus pumilus A3 (350 mg·L −1 ) ( Yanez-Ocampo et al, 2020 ). Through 16S rRNA sequencing, P68 was identified as Bacillus megaterium with 99% homology ( Supplementary Figure S2 ), and improved potato yield and quality in potato roots inoculation with P68 ( Table 1 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In this study, a highly effective P-solubilizing strain was screened and identified as Bacillus megaterium , with a P-solubilizing capacity of 461.86 mg·L −1 after 7 days of incubation in NBRIP medium, which was higher than the Bacillus strain P1 (392.56 mg·L −1 ), P2 (296.77 mg·L −1 ), P58 (371.16 mg·L −1 ), Bacillus subtilis KSP-11 (66.4 mg·L −1 ) ( Hanif et al, 2015 ), and Bacillus pumilus A3 (350 mg·L −1 ) ( Yanez-Ocampo et al, 2020 ). Through 16S rRNA sequencing, P68 was identified as Bacillus megaterium with 99% homology ( Supplementary Figure S2 ), and improved potato yield and quality in potato roots inoculation with P68 ( Table 1 ).…”
Section: Discussionmentioning
confidence: 87%
“…As PSB synthesizing various phytohormones necessary to encourage plant growth, minimizing the use of chemical phosphorus fertilizers, it is essential for the sustainable agricultural development ( Panda et al, 2016 ; Estrada-Bonilla et al, 2021 ). Yanez-Ocampo et al (2020) isolated a strain of Bacillus pumilus A3 from potato rhizosphere soil with phosphorus-solubilizing capacity of 350 mg·L −1 and used it in an in vitro culture trial of potato microplants. The data showed that A3 significantly increased the length of stem and root, and fresh weight of potato.…”
Section: Introductionmentioning
confidence: 99%
“…Five phosphate solubilizer bacterial strains (PSB) were isolated from soil surface samples (at first, 15 to 20 cm in depth) from agricultural soils where potatoes ( Solanum tuberosum ) are grown at Toluca’s Nevado in the Municipality of Zinacantepec, State of Mexico, Mexico (GPS: longitude (dec): - 99.805278, latitude (dec): 19.161389). The PSB screening and isolation were as reported by Yañez-Ocampo et al [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ten, 0.1 ml of the appropriate dilution solution was pipetted into a Petri dish. Diferent types of microorganism-specifc media were used: nutrient agar (NA) for bacteria, actinomycetes isolation agar (AA) for actinomycetes, potato dextrose agar (PDA) for fungi (HIMEDIA), Pikovskaya (PVK) medium for phosphate-soluble bacteria [23], and N-free medium (NF) for nitrogen-fxing bacteria [24]. Microorganisms were counted after incubation at 30 °C for 24 h for bacteria and for 7 days for actinomycetes and fungi.…”
Section: Microbial Countsmentioning
confidence: 99%